2002
DOI: 10.1016/s0014-5793(02)03178-2
|View full text |Cite
|
Sign up to set email alerts
|

Type I chaperonins: not all are created equal

Abstract: Type I chaperonins play an essential role in the folding of newly translated and stress-denatured proteins in eubacteria, mitochondria and chloroplasts. Since their discovery, the bacterial chaperonins have provided an excellent model system for investigating the mechanism by which chaperonins mediate protein folding. Due to the high conservation of the primary sequence among Type I chaperonins, it is generally accepted that organellar chaperonins function similar to the bacterial ones. However, recent studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 47 publications
(62 reference statements)
1
42
0
1
Order By: Relevance
“…Hsp60 is constitutively expressed under normal conditions, but its levels can increase (as determined by immunohistochemical methods for example) in pre-neoplastic lesions (Cappello et al, 2002(Cappello et al, , 2003a(Cappello et al, , 2003bFan et al, 2006) and in many advanced cancers (Schneider et al, 1999;Cappello et al, 2005;Urushibara et al, 2007). The main function of the mitochondrial Hsp60 is considered to be assistance in the folding and degradation of mitochondrial proteins (Garrido et al, 2001;Levy-Rimler et al, 2002;Fersht and Daggett, 2002;Parcellier et al, 2003).The involvement of Hsp60 in the process of apoptosis and tumorigenesis is still under debate. In a recent work, Chandra et al (2007) showed that Hsp60, when it accumulates in the cytosol of tumor cells with significant mitochondrial release, possesses a pro-apoptotic function.…”
Section: Discussionmentioning
confidence: 99%
“…Hsp60 is constitutively expressed under normal conditions, but its levels can increase (as determined by immunohistochemical methods for example) in pre-neoplastic lesions (Cappello et al, 2002(Cappello et al, , 2003a(Cappello et al, , 2003bFan et al, 2006) and in many advanced cancers (Schneider et al, 1999;Cappello et al, 2005;Urushibara et al, 2007). The main function of the mitochondrial Hsp60 is considered to be assistance in the folding and degradation of mitochondrial proteins (Garrido et al, 2001;Levy-Rimler et al, 2002;Fersht and Daggett, 2002;Parcellier et al, 2003).The involvement of Hsp60 in the process of apoptosis and tumorigenesis is still under debate. In a recent work, Chandra et al (2007) showed that Hsp60, when it accumulates in the cytosol of tumor cells with significant mitochondrial release, possesses a pro-apoptotic function.…”
Section: Discussionmentioning
confidence: 99%
“…The Hsp60 family of stress proteins are expressed both constitutively and under conditions of stress and can be classified into two groups -mitochondrial Hsp60 (mHsp60) and cytosolic Hsp60 (cHsp60) (120,121). The mHsp60 forms heptamers and tetradecamers in association with Hsp10 and ATP and is an important part of the mitochondrial chaperone system, while the cHsp60 forms heteroligomeric ring structures to stabilize important cytoskeletal proteins such as actin and tubulin (122,123).…”
Section: Hsp60mentioning
confidence: 99%
“…Type I chaperonins are essential molecular chaperones of the Hsp60 family found in eubacteria, mitochondria, and chloroplasts (1). They are key players in mediating the correct folding of newly translated, translocated, and stress-denatured proteins.…”
mentioning
confidence: 99%